Predictors of residential stability among homeless young adults: a cohort study. (December 2015) - Roy, Élise; Robert, Marie; Fournier, Louise; Laverdière, Émélie; Berbiche, Djamal; Boivin, Jean-François
Abstract Background Homelessness episodes have been shown to be associated with serious health outcomes among youth. This study was undertaken to estimate the probability of reaching residential stability over time and to identify predictors of residential stability among homeless young adults aged 18 to 25 years. Methods A prospective cohort study was carried out in Montréal, Canada, between April 5th 2006 and January 21th 2009. Interviews conducted every three months included questions on life conditions and social and mental health factors that are known to influence residential trajectories. Residential status was determined, starting on the first day after recruitment; each follow-up day was classified as a homeless day or a housed day. A period of 90 days was used to define residential stability; therefore the main study outcome was the occurrence of the first consecutive 90 housed days during the follow-up period. Kaplan-Meier and Cox proportional-hazards regression analyses were conducted. Results Of the 359 participants, 284 reached 90 days of residential stability over the study period, representing an annual probability of 80.5 %. In multivariate analysis, youth who had a high school degree, had a formal sector activity, and those who had sought psychological help were more likely to reach residential stability. Being a man, injecting substances, and having an informal sector activity were associated with a decreased probability to reach residential stability. Conclusion Exposure to factors related to opportunities that promote social integration increases the chance of reaching residential stability. On the other hand, factors related to high level of street entrenchment seem to interfere with stabilization. Maximum efforts should be made to prevent chronic homelessness among youth, targeting not only individual impairments but also hinging on services adapted to foster social connections among the youth.